Chinese mothers' intention to vaccinate daughters against human papillomavirus (HPV), and their vaccine preferences: a study in Fujian Province - Yulan Lin; Zhitai Su; Fulian Chen; Qinjian Zhao; Gregory D. Zimet; Haridah Alias; Shuqiong He; Zhijian Hu; Li Ping Wong (Taylor & Francis Group, 2021)
Little is known regarding Chinese mothers' intention to vaccinate their daughters against human papillomavirus (HPV) since the HPV vaccine was approved for use in China in 2016. The aim was to explore maternal HPV vaccination acceptance, preference for 2-, 4- or 9-valent HPV vaccine and acceptance of domestically manufactured HPV vaccines. Study participants were mothers of primary school children in Southeastern region of Fujian. An online cross-sectional survey was undertaken between June and August 2019. Among the total of 3,586 completed responses (response rate 28.5%), the intention to vaccinate daughter against HPV was high (83.3%). Higher maternal education and perceived benefit and barriers were associated with greater intention to vaccinate. Among mothers who did not intend to vaccinate their daughters, the three most common reasons were daughter being too young to receive HPV vaccination (40.6%), fear of side effects (31.9%) and vaccine price is too high (16.0%). The largest proportion (41.4%) preferred their daughter to be vaccinated with the 9-valent HPV vaccine (9vHPV). Greater preference for 9vHPVwas strongly associated with higher maternal education level and annual household income. The majority of mothers expressed a preference for imported HPV vaccine (56.3%). Our result indicates that lower intentions to vaccinate daughters against HPV among less educated and lower-income mothers may lead to significant social inequalities in HPV vaccine uptake in the country.